The Capacity of Conflict Points Between Double-Track Lines - Čičak, Mirko; Badanjak, Dragan; Kukec, Josip (Promet - Traffic&Transportation, 2002)
The objective of the railway is to offer high level of transportservices, i.e. the quality which is competitive to other transportmodes, but which minimises its internal costs at the same time.In order to increase the capacity of transport services andreduce the costs, splitting of trains between different categoriesof transport on separate railway lines will be more and more appliedin the 21’ centtuy. Unfortunately, even in the developedcountries there will be lines or line sections where mixed trafficwill be cmTied, and in developing countries this will often be thecase even on the main trunk lines.Therefore, a topical issue is to establish the capacity andchoose the right solution. The problem becomes more complexin cases when two double-track lines with mixed traffic need tobe connected and the restructuring of traffic implemented. Atthe same time the exits to two new double-track lines with thespecific train categories have to be ensured and the requiredquality of transport services maintained.In this paper, the impact the capacity has on quality is discussedand some basic characteristics of a model, which enablesthe research of the conflict points capacity, i.e. of convergingand diverging points of two double-track lines is given. Although,there are some analytical elements in this model, it isessentially simulation which enables us to carry out tests underdifferent conditions, to study different variants and to systematisedifferent indicators and make conclusions.